Group career intervention and decision making of adolescents - Galvez, Cynthia S. Siron (2008)
This study investigated the effectiveness of Group Career Intervention in facilitating and enhancing the career decision-making of rural public high school adolescents. Two groups of high school adolescents found to be in need of career assistance were divided to a control group and an experimental group. The latter was exposed to Group Career Intervention whereas the former only with basic career information. Career interests of public senior high school adolescents were more on business, art and the professional areas and were primarily influenced by their parents and peers. Students were much concerned on financial insecurities and lack of financial opportunities. Group Career Intervention is an effective technique in facilitating and enhancing career decision-making of rural public senior high school adolescents.